De la cure des âmes à l’évangélisation des corps. Le CLER Amour et Famille : classes dominantes et morale sexuelle - Gauthier Fradois (Genre, Sexualité et Société)
Essentially composed of women from the Catholic fraction of the dominant classes, CLER Amour et Famille works to promote « ecological » methods of fertility regulation. Created in 1961 against the opening of the first centers of French Movement for Family Planning and backed by the Vatican’s millennial authority, this confessional association intervenes in schools in the private sector in order to dispense by an « emotional, relational and sexual education » representations of the family founded in kind. This article gives an account of the practical logics of these activists of Love who contribute to the struggle for the imposition of a legitimate definition of the meaning of sexuality, by analyzing biographical trajectories.